Dust properties in NGC 6611 - Orsatti, Ana Maria (2000)
An investigation on dust properties in the NW portion of NGC 6611 has been conducted polarimetrically to test the existence of abnormal extinction in that section of the open cluster in an independent way. As previously suggested for the η Carinae nebula by Tapia et al. (1988b) and subsequently confirmed by Marraco et al. (1993), the canonical relation between EV −K/EB−V and λmax (the wavelength of maximun interstellar polarization) is not valid for stars belonging to dusty H ii regions, as is the case for the observed portion of M 16. This may arise mainly from the presence of silicate grains of a slightly larger size than the standard ISM and also from a considerable increase in mean graphite grain size, according to previous results from Chini & Wargau (1990). About 50% of the observed stars in NGC 6611 present indications of intrinsic polarization in their measurements; a similar percentage was found in IC 2944 (Vega et al. 1994), another young open cluster in close relation with an H ii region.